Infográficos: habilidade na leitura do gênero por alunos de ensino médio e ensino superior - Mariana Samos Bicalho Costa Furst (2010)
The ever-growing presence of imagery in media has clearly sparked an interest in information graphics; the main object in this study. Due to the evident lack of linguistic studies on this issue, it was only natural we seek help from various social communication authors. This way we would find a viable and interesting form of contributing to the area of study of information graphics since we believe this genre to be much too complex for it not only displays verbal text but also contains a plethora of semiotic systems. We conceived information graphics to be a textual genre andquestioned it as an existing teaching topic by means of a survey with 10 high school students and 10 college students. This survey produced results which led us to realize that information graphics is not found in Portuguese classes, though it may sometimes be used in other subjects, such as Geography. From the data collected in the survey analysis, a research procedure plan was created; that in which those 20 participantsinvolved in the initial process would read selected information graphics for the development of this study. After the reading of such genre, each participant answered a 12-item questionnaire which tested the development of nine abilities involved in the reading of information graphics. We chose to work with freshman students from colleges and high schools so that we could evaluate any improvement between the twotypes of participant. In other words, we wanted to examine if college students would demonstrate a greater familiarity than the high school pupils. After the implementation of the activities of the first process, we selected a further 30 informants of Higher Education to carry out activities rewrite the genre. Once collected, qualitative and quantitave analysis were made on the results, including statistic evaluations. Thisanalysis showed us that the ability which presented best improvement was identifying information and data on the graphs as well as integrating information between verbal and non-verbal communication whilst the lowest degree of adequation was the ability to infer reasoning over the authors decision. Furthermore, the intention of this studyis to contribute to the increase in the approach of information graphics in the teaching of Portuguese in schools; for we believe learning institutions must properly prepare their students for life; in order to produce duly literate citizens.